Evaluation of “ventilation resilience” in mid-sized office buildings - Assaad, Douaa Al; Breesch, Hilde (CLIMA 2022 conference, 2022)
In industrialized countries, people spend 80-90% of their times indoors, thus, providing them with clean spaces that preserve their wellbeing and productivity is critical. This can be done by delivering scheduled or demand-driven amounts of clean air that dilute the concentration of generated pollutants to adequate levels. However, the building and its ventilation system might be subjected to unpredictable shocks or disturbances (i.e., sudden failure in system components) that compromise the efficiency of the ventilation design, deteriorate indoor air quality and lead to acute exposure events. The ability of the building and its ventilation system to withstand and absorb the shock and maintain the IAQ design conditions is termed as “ventilation resilience”. In this work, a typical open-plan office equipped with a balanced variable-air-volume mechanical ventilation system, is considered. Its ventilation resilience was assessed against power outage shocks and additional occupancy beyond expected peaks. Two types of pollutants were considered (exhaled CO2 and formaldehyde from exhalation and office surfaces). To conduct this study, a Building simulation model was developed for the office and AHU in Modelica using Dymola. Results showed that for the considered shocks, no VOC violations were noted due to low emission rates. This was not the case for CO2: For power outage shocks, the building/ventilation system were resilient for up to 15 minutes of shock and for 1 additional occupant in the space. Beyond those limits, the building/ventilation system are no longer resilient. For 60 minutes of power outage shock, CO2 violations (>900 ppm) of 2 hours were noted with peaks of 1240 ppm while for 6 additional occupants, CO2 violations of 2 hours were noted with peaks of 1150 ppm. A combined shock of these two cases caused 3 hours of violation and peak concentrations of 1747 ppm.